Presidential Elections Without a Threshold in Indonesia: Strengthening Citizens’ Political Rights After the 2025 Constitutional Court Decision - Ropii, Imam; Pramono, Agus; Kuntardjo, Carolina; Kusuma, Ariska Cesar Divian Candra (Fakultas Syariah INSURI Ponorogo, 2026)
The presidential threshold in Indonesia, requiring political parties or coalitions to secure at least 20% of parliamentary seats or 25% of valid votes to nominate presidential candidates, has long sparked debate over the constitution. Critics contend that this requirement operates as a structural barrier that limits citizens' political rights and consolidates oligarchic dominance. This study examines the abolition of the presidential threshold following the Constitutional Court's Decision No. 62/PUU-XXII/2024, which annulled Article 222 of the 2017 Election Law. Employing a normative juridical and comparative approach, the research analyzes constitutional principles, judicial reasoning, and electoral practices in selected democracies, including France and the United States. The analysis demonstrates that removing the presidential threshold broadens political participation, enhances inclusivity, and fosters fairer democratic competition by reducing the dominance of major parties. Although the absence of a threshold may increase the number of candidates and the likelihood of run-off elections, such consequences can be mitigated through appropriate institutional design. Normatively, this study concludes that abolishing the presidential threshold is constitutionally justified and necessary to fully realize citizens' political rights and democratic sovereignty in Indonesia.